Improving the Quality of Teachers Through Subjective Welfare to Maintain Loyalty To Educational Institutions - Fimas Maulana Al-Jufri; Renny Oktafia; Yayuk Fauziyah (International Consortium of Education and Culture Research Studies, 2020)
The development of educational institutions especially Muhammadiyah has increased quite rapidly. The increase in educational institutions must be balanced by the high loyalty of educators in the institution. So to become educators who are loyal to the institution required subjective welfare for educators who are in the institution. This study aims to understand teacher quality improvement through subjective well-being to maintain loyalty to educational institutions. In this study using a qualitative method with a phenomenological approach with four subjects. Data collection is done by interviews and field notes. This research shows that all four subjects have good gratitude with their profession and enjoy their profession as an educator. Work motivation has an effect on individual job satisfaction. The subjective well-being of the four subjects is influenced by the way he views his profession. The subject sees the teacher as a noble, proud, pleasing, and blessing service. Patience, high gratitude, and social support also help the four subjects in reducing negative emotions so that it is easier to achieve satisfaction in their daily lives and work. So that when the subject has subjective well-being or good or high subjective well-being, the level of loyalty to the educational institution will be good and high.